2019
DOI: 10.3389/fonc.2019.00300
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Other Extrinsic Risk Factors Contributing to the Pathogenesis of Cutaneous T Cell Lymphoma (CTCL)

Abstract: The applications of disease cluster investigations in medicine have developed rather rapidly in recent decades. Analyzing the epidemiology of non-random aggregation of patients with a particular disease fostered identification of environmental and external exposures as disease triggers and promoters. Observation of patient clusters and their association with nearby exposures, such as Dr. John Snow's astute mapping analysis in the mid-1800's, which revealed proximity of cholera patients in London to a contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 89 publications
2
48
0
Order By: Relevance
“…6 Clues pointing to attribution of environmental exposure include the concomitant rise in CTCL cases with industrial expansion, increased incidence in nonblood-related relatives, and known associations of occupational chemicals with other hematologic malignancies. [7][8][9] Clustering has been identified in several studies across the globe, including Sweden, 10 Canada, 11,12 Pittsburgh, Pennsylvania, 13 and Texas. 5,14 The analysis in Texas found 3 communities in metropolitan Houston with rates of CTCL that were between 5 and 20 times higher than the expected population rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Clues pointing to attribution of environmental exposure include the concomitant rise in CTCL cases with industrial expansion, increased incidence in nonblood-related relatives, and known associations of occupational chemicals with other hematologic malignancies. [7][8][9] Clustering has been identified in several studies across the globe, including Sweden, 10 Canada, 11,12 Pittsburgh, Pennsylvania, 13 and Texas. 5,14 The analysis in Texas found 3 communities in metropolitan Houston with rates of CTCL that were between 5 and 20 times higher than the expected population rate.…”
Section: Introductionmentioning
confidence: 99%
“…Although approximately 50% of the increase in CTCL can be attributed to increased diagnosis and reporting of these cancers, this does not fully account for the population trends . Clues pointing to attribution of environmental exposure include the concomitant rise in CTCL cases with industrial expansion, increased incidence in nonblood‐related relatives, and known associations of occupational chemicals with other hematologic malignancies . Clustering has been identified in several studies across the globe, including Sweden, Canada, Pittsburgh, Pennsylvania, and Texas .…”
Section: Introductionmentioning
confidence: 99%
“…Demographic and geographic data were obtained from the Canadian Cancer Registry (CCR), Le Registre QuĂ©bĂ©cois du Cancer (LRQC), and the Canadian Vital Statistics (CVS) databases, as described previously. 13,14,[16][17][18][19][20][21][22][23][24][25][26] The CCR is a national database of cancer patients from 12 Canadian provinces and territories (excluding Quebec) who were diagnosed with primary tumors between 1992 and 2014. The LRQC database was used to obtain corresponding data for patients residing in Quebec.…”
Section: Methodsmentioning
confidence: 99%
“…Despite intense research efforts in recent years, the pathogenesis of CTCL still remains poorly understood. Genetic, epigenetic, and environmental factors have all been proposed to be implicated in CTCL [1,4,5]. To date, no studies have identified overarching mutational drivers explaining the pathogenesis of this cancer; however, genetic aberrations may be important in a subset of patients, but are not sufficient to explain the full complexity of CTCL's pathology [6].…”
Section: Etiology Of Cutaneous T Cell Lymphomamentioning
confidence: 99%
“…A comprehensive study, taking advantage of the Danish cohort of twins, suggested that CTCL has very few heritable components, and several lines of evidence indicate that environmental factors may play a promoting or even initiating role in the carcinogenesis of CTCL [5,45]. Accordingly, it may be speculated that exogeneous factors including drugs, pesticides, and bacterial toxins may promote disease progression [5].…”
Section: Dysregulation Of Mirs In Ctclmentioning
confidence: 99%